2003
DOI: 10.1080/0026897021000046889
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and bandwidth of multiphonon vibronic transitions of rare-earth ions in crystals

Abstract: The theory of multiphonon vibronic coupling to electronic transitions is applied in analysing fluorescence spectra of EuZf in BaFCI, which consist of the 4f7(6P7 ,) + 4f7(8S712) and 4f65d + 4f7 transitions, and the 4f74f65d excitation spectrum of Ce-+ in YP04. The 4f electrons are weakly coupled to lattice vibration modes so that only weak one-and twophonon sidebands are observable in the 4f4f optical transitions, whereas the electronphonon coupling is significantly stronger for a 5d electron. Accordingly, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…Liu et al [8] showed that, for vibronic transitions that couple to low-frequency lattice phonon modes, the temperature dependence of the line width can be approximately expressed as…”
Section: Spectral Line Shapementioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al [8] showed that, for vibronic transitions that couple to low-frequency lattice phonon modes, the temperature dependence of the line width can be approximately expressed as…”
Section: Spectral Line Shapementioning
confidence: 99%
“…In many cases, this model can be used to interpret vibronic transitions in a multi-phonon mode lattice where the electronic transition is strongly coupled only to one specific local mode, or the vibrational modes are independent from each other [8].…”
Section: Theoretical Basis Of Multiphonon Vibronic Transitionsmentioning
confidence: 99%
See 3 more Smart Citations